2016
DOI: 10.1002/ana.24794
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of subclinical epileptiform activity in Alzheimer's disease

Abstract: OBJECTIVE Seizures are more frequent in patients with Alzheimer’s disease (AD) and can hasten cognitive decline. However, the incidence of subclinical epileptiform activity in AD and its consequences are unknown. Motivated by results from animal studies, we hypothesized higher than expected rates of subclinical epileptiform activity in AD with deleterious effects on cognition. METHODS We prospectively enrolled 33 patients (mean age 62 years) who met criteria for AD, but had no history of seizures, and 19 age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
471
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 404 publications
(551 citation statements)
references
References 66 publications
33
471
4
4
Order By: Relevance
“…A growing body of evidence suggests that network dysfunction in the form of epileptiform activity contributes to cognitive deficits in AD, even in early stages of the disease (Bakker et al, 2012; Vossel et al, 2013; Vossel et al, 2016). Understanding how specific neuronal alterations contribute to cognitive deficits may therefore highlight additional therapeutic avenues to improve the quality of life for AD patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that network dysfunction in the form of epileptiform activity contributes to cognitive deficits in AD, even in early stages of the disease (Bakker et al, 2012; Vossel et al, 2013; Vossel et al, 2016). Understanding how specific neuronal alterations contribute to cognitive deficits may therefore highlight additional therapeutic avenues to improve the quality of life for AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…This rate may be underestimated due to the incidence of subclinical epileptiform activity and non-convulsive seizures, which in a majority of cases precede or coincide with the diagnosis of amnestic mild cognitive impairment or AD (Vossel et al, 2013). A recent prospective study found that 42.4% of AD patients with no clinical history of seizures exhibited subclinical epileptiform activity, and the presence of such activity was associated with faster rates of cognitive decline (Vossel et al, 2016). Furthermore, multiple mouse models of AD exhibit epileptiform activity (Chin and Scharfman, 2013; Kam et al, 2016; Minkeviciene et al, 2009; Palop et al, 2007; Palop and Mucke, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…[8, 40] The genes included AD-causing mutations (amyloid precursor protein ( APP ), presenilin 1 ( PSEN1 ), and presenilin 2 ( PSEN2 )) and FTD-causing mutations (chromosome 9 open reading frame 72 ( C9ORF72 ), FUS RNA binding protein ( FUS ), granulin precursor ( GRN ), microtubule-associated protein tau ( MAPT ), and TAR DNA binding protein ( TDP43 )). Genetic variants associated with dementia risk and potential genetic disease modifiers were also assessed including apolipoprotein E ( APOE ) alleles,[8], MAPT Ala152Thr (A152T) substitution,[41] granulin precursor rs5848 allele,[42] MAPT H1/H2 haplotype,[8] transmembrane protein 106B ( TMEM106B ) rs1990622 allele,[43] and triggering receptor expressed on myeloid cells 2 ( TREM2 ) rs75932628 allele. [44] Genotype data was available in 25–30% of all 1,846 subjects.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, subclinical epileptiform activity, the occurrence of epileptiform activity in the absence of seizures, can be detected in over 40% of AD patients when they undergo extended neurophysiological monitoring [8]. Both seizures and subclinical epileptiform activity in AD are associated with accelerated cognitive decline [810], a phenomenon that could relate to increased amyloid-beta (Aβ) and tau production due to periodic increases in synaptic activity [1113] as well as chronic compensatory remodeling of neuronal circuits [14, 15]. Previous studies suggest that seizures and myoclonus, which are both signs of network hyperexcitability, could predict shortened survival in AD [16, 17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation